2021
DOI: 10.22334/traverse.v2i2.48
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of semiotic found in the selected skincare advertisement

Abstract: Advertisement is a media that use to promote a product or service for the public. In the advertisement there are signs.. This study concern to analyze the verbal and non-verbal signs found in the skincare advertisement. There two aims of this study such as: (1) to find out the verbal and non-verbal signs in the skincare advertisement, (2) to analyze the meaning of verbal and non-verbal signs of the skincare advertisement. This study use descriptive qualitative method. The data were analyzed based on theory pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The semiotic science variables may be delivered inside the pattern of a hotel advertisement as it offers a top level view of the suitability among the application of semiotics and hotel advertising in the advertisement. The fourth is theses entitled "An Analysis of Verbal and Visual Signs In The Selected Skincare Advertisements" written by Suwitri (2021). This study revealed that there were found 41 verbal signs and 32 non-verbal signs with two research problem which are what verbal and non-verbal sign used in skincare advertisement and what is the meaning of verbal and non-verbal signs in skincare advertisements.…”
Section: Introductionmentioning
confidence: 88%
“…The semiotic science variables may be delivered inside the pattern of a hotel advertisement as it offers a top level view of the suitability among the application of semiotics and hotel advertising in the advertisement. The fourth is theses entitled "An Analysis of Verbal and Visual Signs In The Selected Skincare Advertisements" written by Suwitri (2021). This study revealed that there were found 41 verbal signs and 32 non-verbal signs with two research problem which are what verbal and non-verbal sign used in skincare advertisement and what is the meaning of verbal and non-verbal signs in skincare advertisements.…”
Section: Introductionmentioning
confidence: 88%
“…There were two kind of research problem in this study: What are verbal and Non-Verbal sign occurred in Himalaya Herbals advertisements and what are the meaning of verbal and Non-Verbal signs occurred in Himalaya Herbals advertisements. The second theses with the title "A Semiotic Analysis Found in the Selected Garnier Product Advertisement" written by Putri (2020). In this thesis, there were two research problem which are: what are verbal and non-verbal sign found in selected Garnier product advertisement and what are the meaning of the verbal and non-verbal sign in selected Garnier product advertisement.…”
Section: Introductionmentioning
confidence: 99%

Semiotic Analysis in Victoria Secret Product Advertisements

I Gede Dayuh Suryantara,
I Dewa Ayu Devi Maharani Santika,
Desak Putu Eka Pratiwi
2022
elysian
“…A signifier is a form that takes the sign as the concept, and a signified is a form that takes the verbal and nonverbal sign as the concept. According to Suwitri (2021) Dyer (1993); meanwhile, this study used the theory by Barthes (1967).…”
Section: Introductionmentioning
confidence: 99%